Black Sea Basin Geostrategic Region from History to Modern Times - Bosneagu, Romeo; Scurtu, Ionut Cristian; Lupu, Sergiu; Lupu, Carmen Elena; Patrau, Daniel Daneci; Coca, Carmen Elena (Technium EcoGeoMarine, 2023)
For Black Sea its geostrategic importance has become increasingly evident in recent years, as major powers have become more aware of its potential benefits and risks. The region's location at the crossroads of Europe, Asia, and the Middle East makes it an important trade route and strategic point, connecting different regions and cultures. Its natural resources, such as oil, gas, and minerals, have also attracted the attention of major energy producers and consumers. In addition, the Black Sea has become an important arena for diplomacy, cultural exchange, scientific research, and military affairs. Major powers such as Russia, Turkey, and the United States have increased their presence and influence in the region, seeking to promote their interests and secure their strategic goals. These efforts have included political and economic partnerships, military alliances, and cultural initiatives, among others. These issues require collective action and cooperation among all stakeholders in the region.